P‐216: High efficiency, transparent overcoat for planarization of display modules. Issue 1 (29th May 2019) - Reit, Radu; Nagashima, Noriyuki; Imaizumi, Masahiro; Mori, Satoshi; Yang, Kejia; Vega, Abraham; Avendano, Adrian; Arreaga, David
Abstract : Overcoating materials for the planarization of display module subassemblies such as the thin‐film transistor (TFT) array or the color filter (CF) sub‐pixels have seen little innovation in the previous decade. However challenges with existing overcoat materials still exist, principally in the form of high solvent contents, difficult to remove or toxic solvents and inadequate planarization performance. In response, Ares Materials has employed its Pylux™‐brand polysulfide thermoset (PST) resins as effective overcoat materials which solve the previously described commercial overcoat material issues. In this paper we describe the use of Pylux PST overcoating resins and their corresponding planarization performance over a commercial CF, showing equivalent or improved planarization performance of < 0.2 µm while using > 2X less solvent.